Accounting for Costs, QALYs, and Capacity Constraints: Using Discrete-Event Simulation to Evaluate Alternative Service Delivery and Organizational Scenarios for Hospital-Based Glaucoma Services. (November 2013) - Crane, Glenis J.; Kymes, Steven M.; Hiller, Janet E.; Casson, Robert; Martin, Adam; Karnon, Jonathan D.
Background. Decision-analytic models are routinely used as a framework for cost-effectiveness analyses of health care services and technologies; however, these models mostly ignore resource constraints. In this study, we use a discrete-event simulation model to inform a cost-effectiveness analysis of alternative options for the organization and delivery of clinical services in the ophthalmology department of a public hospital. The model is novel, given that it represents both disease outcomes and resource constraints in a routine clinical setting.Methods. A 5-year discrete-event simulation model representing glaucoma patient services at the Royal Adelaide Hospital (RAH) was implemented and calibrated to patient-level data. The data were sourced from routinely collected waiting and appointment lists, patient record data, and the published literature. Patient-level costs and quality-adjusted life years were estimated for a range of alternative scenarios, including combinations of alternate follow-up times, booking cycles, and treatment pathways.Results. The model shows that a) extending booking cycle length from 4 to 6 months, b) extending follow-up visit times by 2 to 3 months, and c) using laser in preference to medication are more cost-effective than current practice at the RAH eye clinic.Conclusions. The current simulation model provides a useful tool for informing improvements in the organization and delivery of glaucoma services at a local level (e.g., within a hospital), on the basis of expected effects on costs and health outcomes while accounting for current capacity constraints. Our model may be adapted to represent glaucoma services at other hospitals, whereas the general modeling approach could be applied to many other clinical service areas.